Original researchAsymmetrical dimethylarginine and severity of erectile dysfunction and their impact on cardiovascular events in patients with acute coronary syndrome - Aktoz, Meryem; Aktoz, Tevfik; TatlI, Ersan; Kaplan, Mustafa; Nesrin Turan, Fatma; Barutçu, Ahmet; Hüseyin Atakan, Irfan; Demir, Muzaffer; Altun, Armagan (Archives of Medical Science, 2010)
Introduction: Coronary artery disease (CAD) and vascular erectile dysfunction (ED) are related to endothelial dysfunction. Elevated asymmetrical dimethylarginine (ADMA) levels and ED are common in patients with increased cardiovascular risk. Our aim was to investigate whether ADMA has a predictive role for major adverse cardiovascular events (MACE) in acute coronary syndrome (ACS). The secondary aim of this study was to investigate whether severity of ED predicts MACE in these patients. Material and methods: Follow-up data were available for severity of ED in 71 patients with ACS. Plasma ADMA levels were determined by ELISA in 57 patients. Erectile dysfunction was assessed by the International Index of Erectile Function-6 (IIEF-6) score. Major adverse cardiovascular events (reinfarction, all-cause hospitalisation, stroke and all-cause death) was evaluated after a median of 10 months. Results: Severe ED had no significantly increased hazard ratio for cardiovascular events compared with mild, mild to moderate, and moderate ED (0.259 [95% CI 0.041-1.6], p = 0.147; 0.605 [95% CI 0.095-3.8], p = 0.594; 0.980 [95% CI 0.233-4.1], p = 0.978; and 0.473 [95% CI 0.052-1.3], p = 0.508). The patients who had ADMA levels  0.32 µmol/l had no significantly increased hazard ratio for cardiovascular events compared with patients who had ADMA levels < 0.32 µmol/l (2.018 [95% CI 0.615-6.6], p = 0.247). Conclusions: Severity of ED and ADMA did not increase the risk of cardiovascular events in follow-up patients with ACS in our study. Larger prospective studies are necessary to evaluate whether ADMA predicts cardiovascular events in patients with ACS.